Attention Bias and Prodromal Anxiety Symptoms in Toddlers with Fragile X Syndrome and Down Syndrome - Smith, Kayla D. (Am J Intellect Dev Disabil, 2021)
Early identification of behavioral risk markers for anxiety is essential to optimize long-term outcomes in children with neurodevelopmental disorders. This study analyzed attentional avoidance and its relation to anxiety and autism spectrum disorder (ASD) symptomatology during social and nonsocial fear conditions in toddlers with fragile X syndrome (FXS) and Down syndrome (DS). Toddlers with FXS and DS exhibited increased nonsocial attentional avoidance relative to typically developing (TD) toddlers. Attentional avoidance was not related to anxiety symptom severity in any group; however, higher ASD symptom severity was related to more social attentional avoidance in the FXS and TD groups. Findings suggest that there may be different underlying mechanisms driving attentional avoidance across neurodevelopmental disorders.